Genomic profiling identifies GPC5 amplification in association with sarcomatous transformation in a subset of uterine carcinosarcomas. (24th January 2018) - Chui, M Herman; Have, Cherry; Hoang, Lien N; Shaw, Patricia; Lee, Cheng‐Han; Clarke, Blaise A
Abstract: Uterine carcinosarcoma, also known as Malignant Mixed Müllerian Tumour, is a high‐grade biphasic neoplasm composed of sarcomatous elements thought to originate via transdifferentiation from high‐grade endometrial carcinoma. To identify molecular factors contributing to the histogenesis of this tumour, we analyzed DNA extracted from matched carcinoma and sarcoma components from 12 cases of carcinosarcoma by a molecular inversion probe microarray to assess genomic copy number alterations (CNAs) and allelic imbalances. Widespread CNAs were identified in tumours with serous histology in the carcinoma component (9/12), while the remaining three cases with endometrioid carcinoma were near‐diploid. Quantification of the extent of genomic aberrations revealed a significant increase in sarcoma relative to carcinoma in tumours with well‐delineated histologic components. Focal amplification of 13q31.3 was identified in 6/12 profiled tumours, of which four harboured the aberration exclusively in the sarcoma component. This result was verified by fluorescence in situ hybridization against GPC5, the only gene situated within the minimal region of amplification. In a validation cohort composed of 97 carcinosarcomas and other uterine sarcomas, amplification of GPC5 ( GPC5 / CEP13 ratio ≥ 2.2) was identified in 11/97 (11.3%) cases (9/64 carcinosarcoma, 1/3 rhabdomyosarcoma, 1/21 leiomyosarcoma, 0/8 adenosarcoma, 0/1 undifferentiated endometrial sarcoma) and an additional 4 (2.8%) cases had low level gains ( GPC5/CEP13 ratio ≥1.5 but <2.2). The functional relevance of Glypican‐5, the gene product of GPC5, in regulating differentiation and lineage commitment was demonstrated in an endometrial carcinoma cell line in vitro . In conclusion, we identified GPC5 amplification as a molecular event mediating epithelial‐mesenchymal transdifferentiation in a subset of uterine carcinosarcomas.